Functional characterization and transcriptional activity analysis of Dryopteris fragrans farnesyl diphosphate synthase genes - Zhang, Dongrui; Tang, Xun; Chen, Lingling; Qiu, Xiaojie; Song, Chunhua; Wang, Hemeng; Chang, Ying (Frontiers in Plant Science, 2023)
Farnesyl diphosphate synthase (FPS), a key enzyme of the terpene metabolic pathway, catalyzes the precursor of sesquiterpene compounds farnesyl diphosphate (FPP) synthesis, and plays an important role in regulating plant growth and development. Dryopteris fragrans is a medicinal plant rich terpenoids. In the present study, we report the molecular cloning and functional characterization of DfFPS1 and DfFPS2, two FPS genes from D. fragrans. We found that the two genes were evolutionarily conserved. Both DfFPS genes were highly expressed in the gametophyte and mature sporophyte leaves, and their expression levels increased in response to methyl jasmonate (MeJA) and high temperature. Both DfFPS proteins were localized in the cytoplasm and could catalyze FPP synthesis in vitro. We also found that the overexpression of DfFPS genes in tobacco plants promoted secondary metabolite accumulation, but exhibited negligible effect on plant growth and development. However, the transgenic plants exhibited tolerance to high temperature and drought. The promoters of the two genes were amplified using fusion primer and nested integrated PCR (FPNI-PCR). The promoter sequences were truncated and their activity was examined using the β-glucuronidase (GUS) gene reporter system in tobacco leaves, and we found that both genes were expressed in the stomata. The transcriptional activity of the promoters was found to be similar to the expression pattern of the genes, and the transcriptional core regions of the two genes were mainly between -943 bp and -740 bp of proDfFPS1. Therefore, we present a preliminary study on the function and transcriptional activity of the FPS genes of D. fragrans and provide a basis for the regulation of terpene metabolism in D. fragrans. The results also provide a novel basis for the elucidation of terpene metabolic pathways in ferns.